2022
DOI: 10.22458/urj.v14i1.3836
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de un biol sobre las características del suelo y la producción de brotes en pitahaya (Hylocereus sp.)

Abstract: Introducción: Los bioles son fertilizantes líquidos fermentados. Objetivo: Evaluar el efecto de un biol sobre las características del suelo y la producción de brotes, en el cultivo de pitahaya (Hylocereus sp.).  Métodos: Los tratamientos evaluados fueron Fertibiol 45L® y Testigo (agua destilada), ambos aplicados al suelo.  Se realizó un análisis físico, químico y microbiológico del suelo, antes y hacia el final del ensayo. Se evaluó la producción de brotes nuevos (vegetativos y reproductivos), en forma quincen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
0
0
2
Order By: Relevance
“…On the other hand, the pitahaya (Selenicereus undatus), or "Dragon Fruit", has increased its production and export due to the fact that the importing countries of this fruit, such as the United States, Canada, Japan, and the European Union, have managed to consume approximately 17,000 tons in 2018. The growth in demand for the fruit is mainly due to its components, which include glucose, betalains, vitamins, organic acids, soluble dietary fiber, phytoalbumins, and constituent minerals [20]. It has been reported that in 100 g of this fruit, there is water (87 g), protein (1.1 g), fat (0.4 g), fiber (3 g), carbohydrates (11 g), iron (1.9 mg), vitamin B1 (0.04 mg), vitamin B2 (0.05 mg), vitamin B3 (0.16 mg), vitamin C (20.5 mg), calcium (8.5 mg), and phosphorus (22.5 mg), which have appropriate properties for medical and diuretic uses for the benefit of people [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the pitahaya (Selenicereus undatus), or "Dragon Fruit", has increased its production and export due to the fact that the importing countries of this fruit, such as the United States, Canada, Japan, and the European Union, have managed to consume approximately 17,000 tons in 2018. The growth in demand for the fruit is mainly due to its components, which include glucose, betalains, vitamins, organic acids, soluble dietary fiber, phytoalbumins, and constituent minerals [20]. It has been reported that in 100 g of this fruit, there is water (87 g), protein (1.1 g), fat (0.4 g), fiber (3 g), carbohydrates (11 g), iron (1.9 mg), vitamin B1 (0.04 mg), vitamin B2 (0.05 mg), vitamin B3 (0.16 mg), vitamin C (20.5 mg), calcium (8.5 mg), and phosphorus (22.5 mg), which have appropriate properties for medical and diuretic uses for the benefit of people [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Siendo el tratamiento con mayor contenido de N el T2 (dosis: 50 ml/L de EM) con 0.09%, seguido del T3 (dosis: 75 ml/L de EM) con 0.08% y el T1 (dosis: 25 ml/L de EM) con 0.06%. Este comportamiento es debido a que se añadieron microrganismos eficientes, compuesta por una gran diversidad microbiana con capacidad de fijar, solubilizar y liberar elementos como el nitrógeno, potasio, fósforo, azufre, calcio y magnesio (Monge et al, 2022). La fijación del nitrógeno atmosférico en sustrato pudo ser llevaba a cabo por bacterias de vida libre, haciéndola más disponible para las platas de pitahaya.…”
Section: Características Físicas Químicas Y De Contenido De Nutriente...unclassified
“…No obstante, todos los tratamientos presentaron bajos promedios de número de frutos por cada planta de pitahaya, debido a la falta de implementación de un sistema de riego tecnificado que permita el control del aborto floral frente a la exposición a altas temperaturas. Por otro lado, se determinó en la variedad de pulpa blanca con 15 y 21 días de frecuencia de aplicación mayor efectividad en comparación a la variedad de pulpa roja Monge et al (2022). evaluaron el efecto del biol sobre las características del suelo y la producción de brotes tanto vegetativos como reproductivos de pitahaya.…”
unclassified